Leaching and recovery of gold from ore in cyanide-free glycine media. (1st November 2020) - Altinkaya, Pelin; Wang, Zulin; Korolev, Ivan; Hamuyuni, Joseph; Haapalainen, Mika; Kolehmainen, Eero; Yliniemi, Kirsi; Lundström, Mari
Highlights: Leaching and recovery of gold from mildly refractory ore in glycine media was investigated. Temperature and pH have a substantial role in gold dissolution. 90% of gold extracted into the glycine solution after 24 h of leaching. 100% gold recovery from solution could be achieved by carbon adsorption within 4 h. EDRR phenomenon is applicable in principle for gold recovery in glycine media. Abstract: Glycine has recently gained plenty of attention in gold processing as an alternative lixiviant to cyanide due to its non-toxicity, efficiency in metal dissolution as well as selectivity for valuable metals. This paper presents an investigation on the combination of agitated reactor leaching and recovery of gold from mildly refractory ore in cyanide-free alkaline glycine media. Optimal leaching parameters for gold extraction were evaluated using response surface methodology. The investigated parameter range was 0.5–2 M for glycine concentration, pH of 10–12 and temperatures of 23–60 °C, with constant leaching time (24 h) and solid/liquid ratio (100 g/L). Based on the experimental series, a mathematical tool was built to predict gold extraction. It was found that, in the investigated parameter range, glycine concentration did not have a statistically significant effect on gold dissolution. Conversely, both temperature and pH had a substantial role in leaching kinetics. The statistical model suggested that the optimal conditions for gold dissolution were 1.25 M of glycine, pH = 12, and T = 60 °C, corresponding to a predicted 87% gold extraction. The experimental verification showed good reliability of the model with 90% extraction of gold achieved under the predicted optimum conditions. The addition of 15 g/L of activated carbon to the pregnant leach solution (PLS) could provide 100% recovery of gold from solution onto activated carbon, i.e. holistic recovery of 90%. Presence of carbon in leach (CIL) resulted in slightly lower (95%) gold uptake from solution and significantly decreased the holistic gold recovery down to 77%. Additionally, the applicability of direct electrochemical carbon-free recovery method, namely electrodeposition–redox replacement (EDRR), was investigated. In the synthetic solution, a gold recovery as high as 88% was achieved (1247 cycles). However, in the real PLS, only 35% of gold was recovered, which is attributed to different speciation of metals and presence of the other dissolved elements.